On the Job Training (OJT) assessment for Diploma in Construction Technology / Nurhafizah Abdul Musid … [et al.] - Abdul Musid, Nurhafizah; Mohd Affandi, Haryanti; Sohimi, Nurul Eizzaty; Mustaffa Kamal, Mohd Firdaus (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
On Job Training (OJT) is best for skill development and attitude change. Implementation of OJT which focuses on the transition of students to working life, however with little attention given to the process of assessment in OJT. Therefore, the aim of this study is to investigate the OJT assessment problems among Construction Technology students in Malaysian Vocational College. The research design for this study uses a survey that was carried out qualitatively through semi-structured interviews among Construction Technology students, lecturers and experienced construction practitioners. From the data analysis, it has been identified that there is an inadequacy of OJT assessment rubric in assessing the skill and knowledge of the construction technology students. This has been contributed with the used of holistic rubric for the OJT assessment which has been designed to be use by every course in the Vocational College. The result also revealed that allocation of marks in the assessment rubric is not commensurate with some construct assessed and need to be reviewed. This study shows that an assessment rubric should emphasizes on specific knowledge and skills in assessing students’ competency during training program and in this case to produce competent site supervisor. In addition, a good assessment rubric should consider the tasks and marks thoroughly to avoid biasness among students. Therefore, it is suggested to carry out further study in investigating the validity and reliability of current industry’ OJT assessment rubric for the Construction Technology students.